Biomarkers in Pediatric Cardiac Critical Care. (August 2016) - Domico, Michele; Allen, Meredith
Abstract : Objectives: In this review, we discuss the physiology, pathophysiology, and clinical role of troponin, lactate, and B-type natriuretic peptide in the assessment and management of children with critical cardiac disease. Data Source: MEDLINE, PubMed. Conclusion: Lactate, troponin, and B-type natriuretic peptide continue to be valuable biomarkers in the assessment and management of critically ill children with cardiac disease. However, the use of these markers as a single measurement is handicapped by the wide variety of clinical scenarios in which they may be increased. The overall trend may be more useful than any single level with a persistent or rising value of more importance than an elevated initial value.